Effectiveness of the self-tapping relaxation technique on dysmenorrhea pain among nursing students - Veronica Silalahi; Irine Yunila Prastyawati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Menstruation is the discharge of blood, mucus, and cell debris from the uterus at regular intervals with a regular cycle. One of the non-pharmacological methods that can be used to reduce menstrual pain is self-tapping. The phenomenon found in female students of the Emmaus Dormitory in Surabaya, they overcome dysmenorrhea by taking anti-pain medication, consuming traditional herbal medicine